Peran Pengawas Ketenagakerjaan Dinas Tenaga Kerja Provinsi Sumatera Utara dalam Memberikan Perlindungan Hukum atas Kasus Kecelakaan Kerja yang Mengakibatkan Pekerja Meninggal Dunia di PT. Kiat Unggul - Hutagalung, Bangun Nauli; Isnaini, Isnaini; Haikal, M. Ridha (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this paper is to examine and analyze the legal arrangements, roles, and barriers of the labor inspectorate of North Sumatra Province in dealing with labor issues and legal protection for the social security benefits of employment at PT. Superior Tips. This type of research is normative juridical research which refers to the legal norms contained in the legislation. The approach method in this research is used to analyze the research objectives. 3 of 1951 concerning the Statement of Enforcement of the Labor Inspection Law, Regulation of the Labor Inspector in the Regulation of the Minister for Empowerment of State Apparatus No. 30 of 2020 concerning the Functional Position of the Labor Inspector, and the Regulation of the Labor Inspector in the Regulation of the Minister of Manpower Number 33 of 2016 concerning Procedures for Labor Inspection. The role of the Labor Inspector of North Sumatra Province in providing legal protection for the social security benefits for employees at PT. Superior Tips. Barriers faced by the Labor Inspector of North Sumatra Province in providing legal protection for social security benefits at PT. Superior tips can be reviewed from several aspects, namely: Barriers from aspects of legal substance; Barriers from the institutional aspect; Barriers from the aspect of facilities and infrastructure.